2012
DOI: 10.1371/journal.pone.0035616
|View full text |Cite
|
Sign up to set email alerts
|

High Yield Production Process for Shigella Outer Membrane Particles

Abstract: Gram-negative bacteria naturally shed particles that consist of outer membrane lipids, outer membrane proteins, and soluble periplasmic components. These particles have been proposed for use as vaccines but the yield has been problematic. We developed a high yielding production process of genetically derived outer membrane particles from the human pathogen Shigella sonnei. Yields of approximately 100 milligrams of membrane-associated proteins per liter of fermentation were obtained from cultures of S. sonnei Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
154
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 43 publications
4
154
0
Order By: Relevance
“…This was somewhat surprising, considering that cytoplasmic and IM proteins are generally not present or are present only at very low levels in OMVs (4,56). However, GroEL and members of the PDH complex have frequently been detected by proteomics in OMV preparations (57)(58)(59)(60). Our analyses showed that GroEL and PDH-E1 were loosely associated with the OMV surface.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This was somewhat surprising, considering that cytoplasmic and IM proteins are generally not present or are present only at very low levels in OMVs (4,56). However, GroEL and members of the PDH complex have frequently been detected by proteomics in OMV preparations (57)(58)(59)(60). Our analyses showed that GroEL and PDH-E1 were loosely associated with the OMV surface.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, OMV-associated GroEL was detected as an ϳ700-kDa complex upon blue native PAGE (data not shown), consistent with its cytoplasmic tetradecameric form (61). Therefore, and given their frequent association with OMVs and bacterial surfaces (57)(58)(59)(60)62), it is likely that GroEL and PDH-E1 leak from cells under stress conditions and reassociate with bacterial outer membranes or vesicles. Indeed, mild stress could be triggered by the overexpression of Hbp, a notion that is supported by the concomitant upregulation of the outer membrane lipoprotein OsmB, which is encoded by a multistress-responsive gene (63), and of OmpX, which is also known to respond to stress conditions (64).…”
Section: Discussionmentioning
confidence: 76%
“…Two subunit parenteral vaccines are in development to prevent invasive NTS infections among young children in sub-Saharan Africa, including a conjugate consisting of core plus O polysaccharide linked to phase 1 flagellin subunits of the homologous serovar and another consisting of outer membrane particles, called Generalized Module for Membrane Antigens (GMMA) (Gendrivax [http://www.gendrivax.org]) (31,33). Administered parenterally, these vaccines are expected to protect by eliciting functional (likely IgG) antibodies that intercept the invading bacteria during primary bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…2011,2013,2014). OMVs may also contain toxins and other virulence factors (Kulp & Kuehn, 2010 Studies on outer membrane vesicles after imposition of different stresses were found to be different (Berlanda Scorza et al, 2012). OMVs have been used successfully as delivery vehicles for recombinant proteins (Chen et al, 2010).…”
Section: Proteinsmentioning
confidence: 99%